MORTALITY AND PROGNOSTIC FACTORS IN PATIENTS OPERATED FOR ACUTE EPIDURAL HEMATOMA - Khalid, Shah; Shahbaz Ali Khan; Abbasi, Tariq; Khan, Ahsan Aurangzeb; Faiza; Abdul Majid Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Epidural hematoma is one of the most common surgical emergencies encountered in neurosurgery. This study was conducted to determine the mortality and prognostic factors in patients operated for traumatic intracranial epidural hematoma in a resource-constrained setting from a developing country. Methods: This retrospective study was conducted in the Department of Neurosurgery at Ayub Teaching Hospital Abbottabad from 1st January 2019 to 31st Dec 2021. Inclusion and exclusion criteria were created. The medical record of 116 patients admitted and operated on for traumatic extradural hematoma was retrospectively reviewed. Information was recorded using a standardized structured questionnaire. The outcome was measured in terms of the Glasgow coma outcome score. Results: Out of 116 patients, 93 were male and 23 were female.19 (16.4%) patients were in the age range 0-5 years, 42 (36.2%) were in the age range 6-15, 35(31.0%) were in the age range 16-30, 11 (9.5%) were in the age range 31-45 years, 7 (6.0%) were in the age range 46-60 years while only one patient included in this study was above 60 years. Overall mortality was 4.3%. Mortality was higher in females and in those aged less than 5 years (3.4%). 4 out of 16 patients died with GCS less than 8, while none of the patients died when GCS was above 12. Mortality was significantly higher in the presence of associated lesions (4.4% vs. 0%) and anisocoria (2.6% vs.1.7%). Patients who operated within 6 hours of trauma resulted in better outcomes with a mortality rate of 0.0% and functional recovery of 57.8 % while for those who operated after 6 hours, mortality was significantly higher (4.3%) and functional recovery was significantly low (15.5%). Conclusion: Good surgical outcomes can be achieved with early operative intervention if indicated. Female gender, low preoperative GCS score, presence of pupillary dilatation, presence of associated lesions, delayed surgical intervention and age less than 5 years are significant predictors for poor outcomes.